The Determination Of Credit Distribution: A Case Study Of Rural Credit Banks In Indonesia - Ghazali Syamni; Nasir Azis; Alifcha Novanda; Jumadil Saputra (Management Research and Behavior Journal, 2021)
The credit distribution is a vital banking intermediation functions in which banks serve as intermediaries for debtors and creditors. Credit distribution to customers is dependent upon internal and external factors. This research is conducted to examine the influence of internal and external factors on credit distribution at Indonesian’s rural credit banks in particular rural credit banks in Java and Sumatra. The data used in this study are a financial report of rural credit banks in Java and Sumatera from the period 0f 2014-2016 accessed from Bank Indonesia’s website. Inflation data obtained from the Central Bureau of Statistics. This study applies a panel regression model with the common effect model as the best model. The results of the study show that inflation is the single external factor that influences the distribution of assets in BPR, while interest rates (Bank Indonesia’s certificates) do not affect credit distribution. Meanwhile, internal factors which include Operational Costs to Operating Income, third-party funds, Capital Adequacy Ratio, concurrently affect credit distribution in rural credit banks in Indonesia, especially Java and Sumatra.